A Highly Efficient Nonenzymatic Hydrogen Peroxide Electrochemical Sensor Using Mesoporous Carbon Doped ZnO Nanocomposite. Issue 2 (17th February 2021) - Rashed, Md. A.; Faisal, M.; Harraz, Farid A.; Jalalah, Mohammed; Alsaiari, Mabkhoot; Alsareii, S. A.
Abstract : Carbon nanomaterial coupled with inorganic semiconductor based metal oxide is a facile route to develop effective electrochemical sensors. Herein, an electrochemical investigation was carried out for selective and sensitive detection of hydrogen peroxide (H2 O2 ) using 5% mesoporous carbon doped ZnO (Meso-C/ZnO) nanocomposite modified glassy carbon electrode (GCE). The ZnO nanomaterial was synthesized by a F127 structural template agent in a modified sol-gel procedure. Then, a simple ultra-sonication technique was employed to synthesize Meso-C/ZnO nanocomposite. XRD, TEM, FTIR, Raman, and XPS techniques were successfully applied to characterize the as-fabricated nanocomposite. CV and EIS measurements were used to evaluate the electrocatalytic activity of the modified electrode compared to pure ZnO modified GCE and unmodified GCE. The sensing efficiency of the active modified electrode was examined with square wave voltammetry (SWV) technique and the sensor exhibits excellent performance towards the detection of H2 O2 in a wide linear concentration range (from 50 μ M to 981 μ M), with high sensitivity (0.04648 μ M μ A −1 cm −2 ), and low limit of detection (6.25 μ M). Additionally, the selectivity test using several common interfering species demonstrated excellent anti-interfering ability. Furthermore, the fabricated electrode showed excellent reproducibility and operational stability as well as suitability for the real sample analysis. Thus, this new sensor is considered as very auspicious candidate in several fields of science and industry.